Testing A Signaling Theory of Advertising - John W. Maxwell (Queen's University, Department of Economics, 1991)
The signaling theory of advertising predicts that levels of dissipative advertising may be used by a firm to signal to consumers the quality level of its products. This paper develops such a theory within a durable goods framework. It is shown that, subject to refinements of beliefs, the model predicts a strong positive rank order correlation between firm type and the level of dissipative advertising it conducts. Data on the levels of television and total media advertising as well as quality ratings for different model automobiles sold in Canada over the period (1980-1988) are used to test this result using nonparametric procedures.
Keywords: 330